Mini review: Asymmetric Müllerian duct development in the chicken embryo - Tan, Juan L.; Major, Andrew T.; Smith, Craig A. (Frontiers in Cell and Developmental Biology, 2024)
Müllerian ducts are paired embryonic tubes that give rise to the female reproductive tract. In humans, the Müllerian ducts differentiate into the Fallopian tubes, uterus and upper portion of the vagina. In birds and reptiles, the Müllerian ducts develop into homologous structures, the oviducts. The genetic and hormonal regulation of duct development is a model for understanding sexual differentiation. In males, the ducts typically undergo regression during embryonic life, under the influence of testisderived Anti-Müllerian Hormone, AMH. In females, a lack of AMH during embryogenesis allows the ducts to differentiate into the female reproductive tract. In the chicken embryo, a long-standing model for development and sexual differentiation, Müllerian duct development in females in asymmetric. Only the left duct forms an oviduct, coincident with ovary formation only on the left side of the body. The right duct, together with the right gonad, becomes vestigial. The mechanism of this avian asymmetry has never been fully resolved, but is thought to involve local interplay between AMH and sex steroid hormones. This mini-review re-visits the topic, highlighting questions in the field and proposing a testable model for asymmetric duct development. We argue that current molecular and imaging techniques will shed new light of this curious asymmetry. Information on asymmetric duct development in the chicken model will inform our understanding of sexual differentiation in vertebrates more broadly.